2020
DOI: 10.1002/pat.4940
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of electrospun shape memory polyurethane fibers in optimized electrospinning conditions via response surface methodology

Abstract: Herein, the electrospinning method, as an effective approach, was utilized to fabricate poly (ε‐caprolactone)‐based polyurethane (PCL‐based PU) fibers. PCL was synthesized by ring‐opening polymerization, and characterized by proton nuclear magnetic resonance (1H NMR) and Fourier‐transform infrared (FTIR) spectroscopies. Afterward, PU was prepared by step‐growth polymerization. The effects of solution concentration and solvent type on fibers' diameter were investigated. Scanning electron microscopy (SEM) images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The two factors and factor levels were exhibited in Table 2. Based on CCD, an approximate mathematical relationship between the response and the two factors (A: Sphere radius and B: voltage) could be established by the following quadratic polynomial model [27,28]:…”
Section: Response Surface Methods and Design Of Experimentsmentioning
confidence: 99%
“…The two factors and factor levels were exhibited in Table 2. Based on CCD, an approximate mathematical relationship between the response and the two factors (A: Sphere radius and B: voltage) could be established by the following quadratic polynomial model [27,28]:…”
Section: Response Surface Methods and Design Of Experimentsmentioning
confidence: 99%
“…The shape memory performances were earlier thought to be mainly related to the material architecture (e.g., hard‐to‐soft segment concentration in PU systems), [ 141 ] but recent systematic studies [ 145,166,167 ] revealed an important role played also by the fiber morphology: shape fixity, which was overall good (>80%), increases for larger fibers, since the presence of more connection points enhances the stress transfer throughout the fiber networks; [ 145,166,167 ] by contrast, shape recovery of larger fibers may also be very low (25%), and significantly increases for small diameter fibers, due to an effect of the molecular orientation. [ 143,145,166 ]…”
Section: Shape Memory Electrospun Fibersmentioning
confidence: 99%
“…Further research in order to optimize practical parameters was carried out by Banikazemi et al [96] by fabricating shape-memory PCL-based PU fibers and studying the effect of solution concentration, type of solvent, feeding rate, needle-to-collector distance, and applied voltage. Beads-free fibers were obtained with a concentration of 5 w/v% of PU in 60/40 (DMF/chloroform) solvent.…”
Section: Study Of Smp Structure and Propertiesmentioning
confidence: 99%